Constructing Imminent Carcinogenic Attack in English and Arabic Scientific Discourse: A Corpus-Based Contrastive Study (Journal of the College of Education for Women, 2022)
Cancer is one of the critical health concerns. Health authorities around the world have devoted great attention to cancer and cancer causing factors to achieve control against the increasing rate of cancer. Carcinogens are the most salient factors that are accused of causing a considerable rate of cancer cases. Scientists, in different fields of knowledge, keep warning people of the imminent attack of carcinogens which are surrounding people in the environment and may launch their attack at any moment. The present paper aims to investigate the linguistic construction of the imminent carcinogen attack in English and Arabic scientific discourse. Such an investigation contributes to enhancing the scientists’ awareness of the linguistic conduct they follow in attracting people’s attention towards the risk of the approaching attack. The linguistic awareness also helps maintain better promotion of people’s pre-emptive responses that can reduce the potential for cancer cases. To achieve this aim, the paper adopts dual methodological procedures of qualitative and quantitative analyses. Cap’s (2013) proximization theory of threat and crisis construction is adopted for both qualitative and quantitative procedures. The mathematical calculations and statistical results for discourses in both languages are maintained by corpus linguistic analysis using Anthony’s (2019) software, AntConc. The paper has come up to certain conclusions that shed light on the similarities and differences in the construction of the imminent carcinogen attack in both languages. English scientific discourse has shown more reliance on temporal proximization to envisage the imminent attack of carcinogens against human bodies. Categories 1, 2, 3 and 5 are all more dominant in the English scientific discourse. However, both English and Arabic discourses show diversity in the density and employment of the lexico- grammatical tools (categories) that manifest the carcinogen attack.